Editions of the Section for books and graphics of M. Gorky Scientists House of the Russian Academy of Sciences - O. S. Sapunova (Библиосфера, 2015)
The Book and Graphics Section of St. Petersburg Scientists House of the Russian Academy of Sciences is the oldest bibliophile club of the country, which draws to itself attention not only domestic, but also foreign researchers in bibliology nowadays. Besides research and educational activity the Section carried on and is carrying exhibition and publishing activity. More than two hundred exhibitions have been held, more than fifty editions reflecting its member activity have been prepared during its existence.